Revisiting the name, definition and classification of obesity / Harbindar Jeet Singh ... [et al.] - Singh, Harbindar Jeet; Abdul Ghani, Rohana; Ramli, Anis Safura; Durairajanayagam, Damayanthi (Faculty of Medicine, 2024)
The world is facing an escalating epidemic of overweight and obesity, causing a major public health threat in both the developed and developing countries [1]. The World Health Organization (WHO) defines a body mass index (BMI) of between 25 and 30 kg/m 2 as overweight, and a BMI greater than 30 kg/m 2 as obese [2]. Much debate, however, continues on this classification and its applicability to all populations.